The Construction of Heterothallic Strains of Komagataella kurtzmanii Using the I-SceI Meganuclease - Daria D. Sokolova; Philipp I. Akentyev; Kristina O. Petrova; Lyudmila V. Lyutova; Aleksei A. Korzhenkov; Irek I. Gubaidullin; Stepan V. Toshchakov; Dmitry G. Kozlov (Biomolecules)
The methylotrophic yeast Komagataella kurtzmanii belongs to the group of homothallic fungi that are able to spontaneously change their mating type by inversion of chromosomal DNA in the MAT locus region. As a result, natural and genetically engineered cultures of these yeasts typically contain a mixture of sexually dimorphic cells that are prone to self-diploidisation and spore formation accompanied by genetic rearrangements. These characteristics pose a significant challenge to the development of genetically stable producers for industrial use. In the present study, we constructed heterothallic strains of K. kurtzmanii, ensuring a constant mating type by unifying the genetic sequences in the active and silent MAT loci. To obtain such strains, we performed site-directed inactivation of one of the two yeast MAT loci, replacing its sequence with a selective HIS4 gene surrounded by I-SceI meganuclease recognition sites. We then used transient expression of the SCE1 gene, encoding a recombinant I-SceI meganuclease, to induce site-specific cleavage of HIS4, followed by damage repair by homologous recombination in mutant cells. As a result, heterothallic strains designated ‘Y-727-2(alpha)’ and ‘Y-727-9(a)’, which correspond to the α and a mating type, respectively, were obtained. The strains demonstrated a loss of the ability to self-diploidize. The results of PCR and whole genome analysis confirmed the identity of the contents of the MAT loci. Analysis of the genomes of the final strains, however, revealed a fusion of chromosome 3 and chromosome 4 in strain Y-727-2(alpha)-1. This finding was subsequently confirmed by pulsed-field gel electrophoresis of yeast chromosomes. However, the ability of the Y-727-2(alpha)-derived producers to efficiently secrete recombinant β-galactosidase was unaffected by this genomic rearrangement.